2022
DOI: 10.1093/ije/dyac105
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age at birth, chronic conditions and school outcomes: a population-based data linkage study of children born in England

Abstract: Introduction We aimed to generate evidence about child development measured through school attainment and provision of special educational needs (SEN) across the spectrum of gestational age, including for children born early term and >41 weeks of gestation, with and without chronic health conditions. Methods We used a national linked dataset of hospital and education records of children born in England between 1 Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In a study using linked administrative health and education data from England, children with cardiovascular conditions including CHD had a greater cumulative incidence of special education needs provision by age 11 than children without a chronic health condition, both for those born at 40 weeks (50.1% versus 28.8%) and preterm (68.0% versus 48.0% at 24-32 weeks). 12 Survival of children born with CHD into childhood and adulthood increased dramatically in the 20th century. 13,14 Improvements in surgical and clinical management of CHD (e.g.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using linked administrative health and education data from England, children with cardiovascular conditions including CHD had a greater cumulative incidence of special education needs provision by age 11 than children without a chronic health condition, both for those born at 40 weeks (50.1% versus 28.8%) and preterm (68.0% versus 48.0% at 24-32 weeks). 12 Survival of children born with CHD into childhood and adulthood increased dramatically in the 20th century. 13,14 Improvements in surgical and clinical management of CHD (e.g.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…CHD is also associated with more complex educational needs. In a study using linked administrative health and education data from England, children with cardiovascular conditions including CHD had a greater cumulative incidence of special education needs provision by age 11 than children without a chronic health condition, both for those born at 40 weeks (50.1% versus 28.8%) and preterm (68.0% versus 48.0% at 24–32 weeks) 12 …”
Section: Introductionmentioning
confidence: 99%
“…(Participant i10, Hunter, 2022, p66) Such indications of social inequity are at odds with the impact presumably intended by the Department for Education's retention of discretionary deferred entry-which assumedly is not that only the informed and privileged should benefit, but that children who would feasibly be better served by education with the cohort below should access this placement when appropriate (Department for Education, 2021b). Bliss, a campaign group for babies born prematurely (who are gestationally younger and who are more likely to have disabilities and 'special educational needs' [Alterman et al, 2021;Libuy et al, 2022;Mackay et al, 2010]) emphasise the desirability of the option. They have 'argued for many years for greater flexibility, particularly for children who are born premature in the summer months and have fallen into a different school year group as a result' (Bliss, online, nd).…”
Section: Implications For Policy-makersmentioning
confidence: 99%
“…In England, 7.4% of babies were reported as being born premature (pre‐37 weeks gestation) in 2020 (calculated using data from ONS, 2022). The NPD contains no information on due date or prematurity, but there is an overlap between groups of children born premature and those reported with SEND (Alterman et al, 2021; Libuy et al, 2022; Mackay et al, 2010)—so some premature children should be captured within the SEND variable.…”
Section: Data Variables and Approach To Analysesmentioning
confidence: 99%
“…Compared with their peers, children with recorded SEN provision experience higher rates of chronic physical and mental health conditions and hospitalisations, and have lower self-reported well-being 10–12. Recent evidence reviews found that classroom-based SEN interventions improved children’s social, emotional well-being and reduced challenging behaviour, and contributed to better mental health outcomes 13 14.…”
Section: Introductionmentioning
confidence: 99%